USING PROJECT-BASED LEARNING IN TEACHING ENGLISH FOR TOURISM (Multidisciplinary Journal of Science and Technology, 2025)
This paper explores the application of Project-Based Learning (PBL) in teaching English for tourismstudents. The tourism industry requires professionals who can communicate effectively in Englishand solve real-life problems creatively. Therefore, PBL provides a learner-centered framework thatintegrates language skills with practical, tourism-related projects. The paper discusses theoreticalfoundations, implementation strategies, challenges, and pedagogical benefits of PBL in English forTourism (EFT) contexts. The findings suggest that PBL enhances language proficiency, criticalthinking, collaboration, and intercultural competence, making it an effective method for preparingstudents for real-world communication in tourism